2019
DOI: 10.3390/cancers11060743
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Cyclooxygenase-2 in Pheochromocytoma and Paraganglioma: Focus on Genetic Background

Abstract: Cyclooxygenase 2 (COX-2) is a key enzyme of the tumorigenesis-inflammation interface and can be induced by hypoxia. A pseudohypoxic transcriptional signature characterizes pheochromocytomas and paragangliomas (PPGLs) of the cluster I, mainly represented by tumors with mutations in von Hippel–Lindau (VHL), endothelial PAS domain-containing protein 1 (EPAS1), or succinate dehydrogenase (SDH) subunit genes. The aim of this study was to investigate a possible association between underlying tumor driver mutations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Additionally, the role of COX-2 in CSC survival and recolonization after therapy has been considered in detail elsewhere, making it clear that inhibiting COX-2 is an effective way to prevent treatment failure due to tumor repopulation [161]. Addressing COX-2 by selective inhibitors or dual drugs as an adjuvant approach is also feasible in NENs [162][163][164][165].…”
Section: Hif Signalingmentioning
confidence: 99%
“…Additionally, the role of COX-2 in CSC survival and recolonization after therapy has been considered in detail elsewhere, making it clear that inhibiting COX-2 is an effective way to prevent treatment failure due to tumor repopulation [161]. Addressing COX-2 by selective inhibitors or dual drugs as an adjuvant approach is also feasible in NENs [162][163][164][165].…”
Section: Hif Signalingmentioning
confidence: 99%
“…COX-2 is inducible by cytokines, tumor promotors, and growth factors, whereas constitutive expression is limited to kidneys, brain, the gastro-intestinal tract, and thymus [ 21 , 22 , 23 ]. Often overexpressed in tumors, COX-2 is involved in the regulation of cell proliferation, migration, angiogenesis, apoptosis, metastasis, and immune resistance of tumor cells [ 12 , 13 , 14 , 24 , 25 ]. Different studies reported that the reduction in prostaglandin E2 synthesis in tumors by non-steroidal anti-inflammatory drugs (NSAIDs) or COX-2 inhibitors is associated with chemo-preventive effects in some tumors, such as colon, breast, prostate, lung, head, and neck cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclooxygenase-2 converts arachidonic acid to prostaglandin H 2 , and by that, produces the key intermediate in the synthesis of prostanoids and thromboxane A 2 [ 8 ]. While COX-2 gene expression is nearly absent in most healthy tissues, it can be induced by pro-inflammatory mediators during acute and chronic inflammatory states as well as in tumor progression and metastasis, exemplified by malignant melanoma [ 9 , 10 ]. In addition, COX-2 is discussed to be responsible for poor response of various types of cancer in radiotherapy [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…COX-2 exists beside its constitutively expressed isoform COX-1, which shares the same reaction specificity but is mainly involved in homeostatic processes and protection of gastric mucosa. In principle, the analgesic, anti-pyretic, and anti-inflammatory action of COX inhibitors that are classified in nonsteroidal anti-inflammatory drugs (NSAIDs) or selective COX-2 inhibitors (COXIBs) can be attributed to the inhibition of COX-2, while the gastrointestinal toxicity after long-term use especially of NSAIDs results from the concomitant inhibition of COX-1 [ 8 , 9 , 12 , 13 ]. Currently, only selected COXIBs such as celecoxib, etoricoxib, or the prodrug parecoxib are on the market due to an increased risk for cardiovascular incidents such as stroke and heart attacks described after long-term treatment with, e.g., rofecoxib or valdecoxib.…”
Section: Introductionmentioning
confidence: 99%